ENGLISH BORROWING WORDS IN INDONESIAN DAILY CONVERSATION - Ilinawati Ilinawati; Yokie Prasetya Dharma (STKIP Persada Khatulistiwa Sintang, 2018)
The study was about the English borrowing words in Inonesian daily conversation. The subject of the study were the students who were joining the English Activity club, which consisted of 20 students. This study was aimed at (1) the process of English borrowing in Indonesian , (2) the forms of English borrowing in Indonesian (3) the meaning of English borrowing in Indonesian and (4) the reason of English borrowing words in Indonesian. The method of this research was qualitative research and the object was English borrowing words in Indonesian found in students conversation in English. To analyze the data, the writers classified the form of borrowing and classified the meaning of borrowing words.The study showed that the borrowing could be classified into three types; loan words, loan blends and loan shifts.Loan words consisted of target, solusi , adaptasi, akademik. Loan blends consisted of photokopi, antre, pabrik and krah. Loan shifts consisted of kerja sama , rumah sakit.There were two reason of borrowing the words, cultural borrowing and core borrowings. Cultural borrowing are words that fill gaps in the recipient language’s store of words because they stand for objects or concepts new to the language’s culture. Core borrowings are words that duplicate elements that the recipient language already has in its word store. They are gratuitous – by definition, another layer on the cake, because the recipient language always has viable equivalents.Key words: Borrowings, loan words and loan blends, loan shift.